Mental health amongst undergraduate students at IIUM - Abd Razak Al-Hafiz, Afareez; Ismail, Nik Ahmad Hisham (Institut Terjemahan dan Buku Malaysia, 2016)
The purpose of the study is to develop indicators of mental health for Institutional Higher Learning and to explore factors that contribute to mental health issues and concerns.